2018
DOI: 10.21323/2618-9771-2018-1-2-55-62
|View full text |Cite
|
Sign up to set email alerts
|

Chitin- And Chitosan Biosorbents From Citric a Cid Mycelial Industrial Waste

Abstract: The goal of this study is to examine sorption capacity of chitin-glucan (ChGC) and chitosan-glucan (CsGC) biopolymer complexes extracted from the fungus Aspergillus niger mycelium. According to the findings chitosanglucan complex sorbs lead and copper ions (130–140 mg/g) better than chitin-glucan complex (50–80 ex mg/g). Langmuir theoretical model with R2= 0,996 determination coefficient well describe sorption isotherms. It is shown the chelate complex formation compound character based on ion and coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…It is possible that at an earlier stage of the process the content of β-glucans is different and, accordingly, the ratio of glucan and chitin components of HGC, occupying 40 -50 % of the dry matter of the cell wall, also changes. Earlier studies have shown that successive alkaline and acidic effects on Aspergillus biomass lead to deproteinization, deacetylation and ensure the availability of chitin and glucan copolymers of HGC for enzymes with different specificity of action [19]. Comparatively, exposure to endo-(1→3)(1→4)-β-glucanase T. Longibrachiatum, which has the specificity of action to non-starch polysaccharides (hemicelluloses and cellulose cleavage products), is more pronounced in HGC from biomass obtained during fermentation of starch-containing medium.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that at an earlier stage of the process the content of β-glucans is different and, accordingly, the ratio of glucan and chitin components of HGC, occupying 40 -50 % of the dry matter of the cell wall, also changes. Earlier studies have shown that successive alkaline and acidic effects on Aspergillus biomass lead to deproteinization, deacetylation and ensure the availability of chitin and glucan copolymers of HGC for enzymes with different specificity of action [19]. Comparatively, exposure to endo-(1→3)(1→4)-β-glucanase T. Longibrachiatum, which has the specificity of action to non-starch polysaccharides (hemicelluloses and cellulose cleavage products), is more pronounced in HGC from biomass obtained during fermentation of starch-containing medium.…”
Section: Discussionmentioning
confidence: 99%
“…В качестве объектов исследования использованы образцы хитозана, полученные по разработанному способу [13] из мицелиальной биомассы гриба Aspergillus niger. Клеточная стенка гриба Aspergillus niger содержит хитин-глюкановый комплекс, из которого выделен хитозан.…”
Section: экспериментальная частьunclassified
“…Наиболее изучено ММР хитозана, полученного из панцирей ракообразных [9,10]. Нами разработана схема получения хитозана из мицелиальной массы гриба Aspergillus niger -продуцента лимонной кислоты [11]. Исследование его молекулярно-массовых характеристик представляет собой научный и практический интерес.…”
Section: Introductionunclassified
“…Chitosan -poly-β-(1,4)-d-glucosamine is a deacetylated product of chitin -poly-β- (1,4)-N-acetyl-d-glucosamine, one of the most abundant natural polysaccharide, found in composition of crustacean shells and fungal cell walls [1]. There is great scientific and practical interest in chitin and chitosan caused to the unique properties as biocompatibility, safety, biodegradability, sorption performance of heavy metals and radionuclides [2]. Scientific publications amount related to chitin and chitosan is increasing annually and several scientific papers related to its production and application are published weekly according to the Web of Science and Google Scholar.…”
Section: Introductionmentioning
confidence: 99%